The Effect of Hydrotherapy : Foot Soak on Lowering Blood Pressure of Preeclampsia Pregnant Women at Aura Syifa Hospital Kediri - Isnaeni, Ely; Margaretta, Sheylla Septina; Astutik, Wahyu Sri (Adi Husada Nursing Journal; Vol 9 No 1 (2023): Adi Husada Nursing JournalDO - 10.37036/ahnj.v9i1.393, 2023)
Preeclampsia is a condition of pregnant women who tend to be high so they are at greater risk of developing hypertension. This is mostly caused by maternal age and gestational age. Preeclampsia can be treated with nonpharmacological methods, one of which is foot hydrotherapy. The study aims for knowing the influence of hydrotherapy: foot soaks against drop pressure blood on a mother pregnant with preeclampsia at Aura Syifa Hospital Kediri. Type study This use study Pre Experimental Design with design research used One Group Pretest and Posttest Design with 21 respondents with use Purposive sampling technique using sheet research instrument observation and analysis with the Wilcoxon test. Pretest and posttest analysis produce a drop in pressure blood on the first day of 0,8. Decrease pressure pre-intervention blood and post-intervention day second of 0,85. whereas descent pressure pre-intervention blood and post-intervention day third of 0,71. with a value of 0,000, which means there is an influence of foot hydrotherapy against drop pressure blood on a mother pregnant with preeclampsia at Aura Syifa Hospital Kediri. Hydrotherapy using warm water to soak the feet can dilate blood vessels, and reduce muscle tension so that blood flow becomes smooth.